Mathematical thinking in Arabic grammar A study in the light of modern linguistics - Alaa Abed Naeem , Pro. Dr. (lark, 2023)
It is often said: Arabic grammar is a normative grammar that does not deviate from those templates imposed on it by the restrictions of the grammatical rule that represented the justified reasons in the process of preserving Arabic melody and preserving tongues from melody. Infrastructure) and other questions that affect the mechanisms of the mathematical curriculum, the academic curriculum that was explained in its steps to the Arabic grammar approach, what we contemplated the issues of both sciences for our luck, starting with both of them are based on the processes of startup, operation, estimation, substitution, probability, and clear research, then conclusion